All Days 2010
DOI: 10.2118/138366-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Wettability on Oil Recovery From Naturally Fractured Oil Reservoirs Including Non-Equilibrium Effects

Abstract: In the laboratory, partially water-wet systems are often mistaken for completely oil-wet systems, because imbibition only starts after removal of the oil layer, which originally covers the grains. The (long) time required to remove the oil film will be referred to as delay time. Incorporation of delay time in a more general description of capillary pressure and relative permeability functions is called the non-equilibrium effect. No attempt has yet been made to model non-equilibrium effects in fractured reserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 75 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…Naturally fractured reservoirs (NFRs) play an important role in petroleum industry in the world (Yu et al, 2009;Salimi and Bruining, 2010;Chahardowli et al, 2013). In comparison with the conventional reservoirs, NFRs consist of two systems: Fracture and matrix systems (Rangel-German and Kovscek, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Naturally fractured reservoirs (NFRs) play an important role in petroleum industry in the world (Yu et al, 2009;Salimi and Bruining, 2010;Chahardowli et al, 2013). In comparison with the conventional reservoirs, NFRs consist of two systems: Fracture and matrix systems (Rangel-German and Kovscek, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of wettability during recovery processes and enhanced oil recovery simulations has been stated previously in several literatures. For instance, a simulation study conducted by Salimi and Bruining [2] concluded that water-flooding results in low recovery in naturally fractured oil wet reservoirs as compared to water wet reservoirs. Certain wettability is favored in various reservoirs and production processes.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally fractured reservoirs contain about 50% of the world's oil resources, but only about 20% of the world's oil reserves and production (Firoozabadi, 2000, Roehl and Choquette, 1985, Saidi, 1983, Salimi and Bruining, 2010, Yu et al, 2009. Almost all reservoirs contain at least some natural fractures (Aguilera, 1995, Nelson, 2001.…”
Section: Introductionmentioning
confidence: 99%